Ecological Taxation and its role in achieving sustainable development in Algeria - عبد القادر, بوعزة; دحو, عامر حاج (Journal of Economics and Administrative Sciences, 2025)
This study aimed to clarify the importance of ecological taxation in achieving sustainable development, by analyzing a set of economic measures such as taxes, taxes levied by the legislation in the field of ecology, to fight against pollution.       And we tried to evaluate this initiative in Algeria. The results of the study showed that economic measures of ecological taxation contribute to achieving sustainable development, and Although Algeria has adopted a series of ecological tax mechanisms, it is far from keeping pace with developments in this area.